Correlation of HbA1c and S. creatinine along with microbiological profiling of infected ulcers; cases of diabetic patients. Issue 1 (January 2019) - Zubair, Mohammad; Malik, Abida; Ahmad, Jamal
Abstract: Statement of the problem: The rate of diabetes mellitus is increasing globally as a result of increased levels of blood glucose. The elevated blood glucose level results due to impairment in the production and action of insulin. An increase in glycated hemoglobin is associated with higher blood glucose levels that further results in nephropathy, neuropathy, retinopathy, and cardiovascular disease. Therefore, the study has investigated the correlation between HbA1c and creatinine levels among diabetic patients, suffering from foot ulcerations. Methods: A prospective cohort hospital based-study has retrieved hospital records of patients during January 2009 and February 2015. A total of 192 patients, admitted in the Rajiv Gandhi Centre for Diabetes and Endocrinology, of Jawaharlal Nehru Medical College Hospital, Aligarh Muslim University, Aligarh, India were recruited. Results: It has been examined that there is a positive correlation between ulcer duration and BMI, amputation rate and BMI, gender and BMI, hospital stay and BMI, HbA1c and BMI, Hb and BMI and triglyceride and BMI at 5% level of significance. Conclusion: Findings have shown positive association with gender, diabetes duration, ulcer size, grade of ulcer, amputation rate, hospital stay, Hb, SGOT/AST and triglyceride.